Symbiosis Mechanism of Academic Journals and Discipline Construction in Chinese Colleges - Weiling Li; Hong Gao (Discrete Dynamics in Nature and Society)
Academic journals and discipline construction in colleges are two major drivers of scientific progress. There is a complex interactive mechanism between the two drivers. The synergy between the two is worthy of in-depth research. The research aims include better developing academic journals with discipline advantages and back-feeding discipline construction with academic journals. The symbiotic theory provides a new research perspective for the cooperation mechanism between college academic journals and discipline construction. Drawing on the symbiotic theory, this paper explores the root causes and interactive logic of the collaboration between college academic journals and discipline construction, from the angles of the symbiotic unit, symbiotic environment, and symbiotic model. The results show that the symbiosis between academic journals and discipline construction in Chinese colleges mainly relies on two essential parameters, namely, academic talents and research results; although colleges provide a positive environment, the symbiosis between the two factors mostly takes place on unofficial information platforms and cooperation mechanisms, for the relevant policies are relatively new and mostly discipline-oriented; the symbiosis between college academic journals and discipline construction is mutualistic but remains in the intermittent stage. Therefore, it is important to find a more effective symbiotic path for college academic journals and discipline construction, following their symbiotic law.